Biofilm Formation in Dairy: A Food Safety Concern—Recent progress in antibiofilm strategies in the dairy industry - Coralie Goetz; Laurie Sanschagrin; Eric Jubinville; Mario Jacques; Julie Jean (Journal of Dairy Science, 2025)
ABSTRACT: Biofilm formation allows microorganisms including bacteria to persist on abiotic or biotic surfaces, to resist treatments with biocides (disinfectants and antibiotics), and to evade the immune response in animal hosts much more than they do in the planktonic form. Bacteria able to form biofilm can be troublesome in the dairy industry, both by causing clinical symptoms in livestock and by colonizing milking devices and milk processing equipment, resulting in dairy products of lower quality and sometimes raising serious food safety issues. In fact, most of the bacterial species isolated frequently in the dairy chain have the ability to form biofilm. Common examples include Staphylococcus aureus and other staphylococci that frequently infect mammary glands but also Bacillus spp., Listeria monocytogenes, and Pseudomonas spp., which cause spoilage of dairy products and sometimes foodborne illnesses. The economic losses due to biofilm formation in the dairy industry are considerable, and scientists are constantly solicited to develop new antibiofilm strategies, especially using biocides of natural origin. Although the number of studies in this subject area has exploded in recent years, the in vivo efficacy of most novel approaches remains to be explored. Used alone or to increase the efficacy of disinfectants or antibiotics, they could allow the implementation of strategies having less impact on the environment. Their use is expected to lead to less reliance on antibiotics to treat intramammary infections in dairy farms and the use of lower concentrations of chemical disinfectants in dairy processing plants.